Prospective pilot study to identify psychological factors influencing peri-operative pain in total knee arthroplasty (TKA) - Schuster, Verena; Kinne, Raimund W.; Knoll, Natascha; Koenczoel, Clemens; Anders, Jens (International Orthopaedics, 2020)
Purpose Up to 20% of total knee arthroplasty (TKA) patients remain dissatisfied, with chronic pain as the most frequently named cause. A pilot study was conducted to assess the progression of peri-operative pain intensity and the parallel development of different psychological factors and coping strategies, as well as correlations indicating potential inter-relationships. Methods Pain, psychological impairment [FESV BE], and coping strategies [FESV BW] were assessed before and after TKA [days - 5 to 31]. Patients were stratified according to the presence or absence of peri-operative pain improvement [decreasing pain: Group 1 [69%; n = 36]; persisting pain: group 2 [31%; n = 16]]. Group 2 was additionally tested with the Toronto Alexithymia Scale [TAS] and Screening for Somatoform Disorders [SOMS]. Results Pain intensity in group 1 decreased from significantly higher pre-operative levels to significantly lower values at 31 days post-operatively, whereas group 2 did not show significant changes. Concurrently, the psychological impairment parameter anxiety (AN) significantly decreased and the pain coping parameter relaxation significantly increased in group 1, but not in group 2. Whereas pre-operative pain was positively and significantly correlated with AN throughout time in group 2, it was negatively correlated with relaxation at day 29 in group 1. Concerning TAS and SOMS, considerable percentages of the participants in group 2 (37.5% and 68.75%, respectively) showed values > 50% of those in normal controls. Conclusions Parallel (or anti-parallel) and partially correlated developments of pain improvement and parameters of psychological impairment or coping strategies after TKA suggest a pre-operative screening with tools like the FESV BE and BW or TAS and SOMS questionnaires in order to classify individuals for peri-operative mental training.
CRIS-Team WoS Importer:2020-04-24